Trends in paediatric speech audiometry: a scoping review - Zakaria, Nur 'Azzah; Jamaluddin, Saiful Adli; Che Mat Amin, Nur Syakirah; Wan Ahmad, Wan Aslynn Salwani; O’Beirne, Greg A. (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2023)
Speech tests are essential assessment tools of auditory abilities for both adults and children. A scoping review was conducted with the aim to explore possible changes in materials and methods of paediatric speech tests between 1980 and 2019. Thirty-eight articles were selected, and the extractions of information were made related to the name of the paediatric speech test, country of origin, year of publication, language used in the speech test, the target age range for the speech test, and the procedural parameters. Exploration of the articles provided insights into current trends of paediatric speech test applications that should be taken into careful consideration when developing a new speech test for children.